2019
DOI: 10.3389/fcvm.2019.00034
|View full text |Cite
|
Sign up to set email alerts
|

Interventricular Differences in Action Potential Duration Restitution Contribute to Dissimilar Ventricular Rhythms in ex vivo Perfused Hearts

Abstract: Background: Dissimilar ventricular rhythms refer to the occurrence of different ventricular tachyarrhythmias in the right and left ventricles or different rates of the same tachyarrhythmia in the two ventricles. Objective: We investigated the inducibility of dissimilar ventricular rhythms, their underlying mechanisms, and the impact of anti-arrhythmic drugs (lidocaine and amiodarone) on their occurrence. Methods: Ventricular tachyarrhythmias were induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The results in the above mentioned study (2) have shown exclusively LV>RV scenarios. A possible suggestion that was mentioned, would be to change the detection from the right to the left side.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…The results in the above mentioned study (2) have shown exclusively LV>RV scenarios. A possible suggestion that was mentioned, would be to change the detection from the right to the left side.…”
mentioning
confidence: 84%
“…In a recently published article in this journal entitled “Interventricular Differences in Action Potential Duration Restitution Contribute to Dissimilar Ventricular Rhythms in ex vivo Perfused Hearts”, Handa et al used rat hearts to investigate the inducibility of dissimilar rhythms, the impact of antiarrhythmic drugs and the underlying mechanism (2). The authors correctly defined dissimilar ventricular rhythms as the occurrence of different ventricular tachyarrhythmias in the right and left ventricles, or different rates of the same arrhythmia in the two ventricles.…”
mentioning
confidence: 99%
“…Ventricular APs differ in waveform, duration, and dynamics among species and, within the same species, between the right and left ventricle and among different ventricular regions [ 2 , 51 , 57 , 73 , 135 ]. Electrical restitution is subject to analogous heterogeneity [ 19 , 101 , 143 ].…”
Section: Brief History and Main Features Of Cardiac Cellular Ermentioning
confidence: 99%